Digital Marketing Socialization in Building a Business Mentality from an Early Age in High School Students Throughout Indonesia - Sumardi, Sumardi; Siska, Emi Yulia; Permana, Ujang; Putra, Wira Pramana; Tarjono, Tarjono (Journal Of Human And Education (JAHE), 2024)
Digital marketing is promotional activities and market search through online digital media by utilizing various means such as social networks. Social media is growing very rapidly nowadays because everyone feels like they can have their own media. Social media also does not escape the various functions that we can take on, such as building relationships, opening and looking for jobs, and also doing business with social media. The most relevant business strategy in the marketing aspect uses digital tools or known as digital marketing, namely marketing methods carried out using digital instruments, especially the internet and the various applications contained in it and equipment that supports the use of these media, which allows the creation of a network or connectedness with many parties, in this case between sellers and customers, without being limited by distance, time and place. In today's modern era, the potential for entrepreneurship among young people is very large. Because the role of the younger generation in building the nation is very large, the young generation's broad way of thinking can make changes and can be a pioneer in creating new things. This Community Service was carried out at Senior High School Number 8 Tamalate District, Makassar City, South Sulawesi. In obtaining the data used were observation and literature study. This service activity is an effort to build a business mentality from an early age in high school students at Senior High School Number 8 Tamalate District, Makassar City, South Sulawesi through Digital Marketing Socialization. This effort was motivated by the lack of implementation of the formation of a business mentality at a young age for students who want to start a business at a young age through digital marketing at Senior High School Number 8 Makassar. As a form of the author's thinking, several efforts and breakthroughs are offered, namely; 1.) Children are given mental reinforcement on how to become entrepreneurs at a young age, 2.) Increase the income of high school students who want to start a business at a young age through digital marketing as a promotional tool to create business opportunities for students so that students are able to compete and create entrepreneurs youth and open up job opportunities.